Resolutions of IAE (First International Congress of Egyptology, 1979)
Purpose To assess the structural and functional outcomes of treatment with ciliary neurotrophic factor for patients with Type 2 macular telangiectasia (MacTel). Methods Studies were retrieved from inception to May 2024 from MEDLINE, Embase, and Cochrane Library databases. The primary outcome was final best-corrected visual acuity and changes in best-corrected visual acuity from baseline, while ellipsoid zone discontinuity area was a secondary outcome. Risk of bias for observational studies and randomized clinical trials were assessed using the ROBINS-1 tool and Cochrane ROB2 tools, respectively. Results Five studies reporting on 498 eyes of 422 patients were included in this systematic review. One randomized clinical trials of 99 eyes found decreased progression of retinal degeneration and reduced decline in reading speed in implant-treated eyes compared with sham-treated eyes. An uncontrolled Phase 1 safety trial involving 14 eyes in 7 patients with MacTel undergoing ciliary neurotrophic factor therapy demonstrated good tolerance, with no significant differences in visual acuity or retinal sensitivity between treated and untreated eyes over 36 months, although five participants experienced persistent miosis in the implanted eye. One study highlighted smaller changes in ellipsoid zone defect areas in ciliary neurotrophic factor-treated eyes compared with sham-treated eyes. Recently published data demonstrated significant structural progression slowing, although functional outcomes were variable and safety was comparable with sham aside from increased delayed dark adaptation and miosis. Conclusion Ciliary neurotrophic factor therapy seems to slow retinal degeneration and preserve visual function in patients with MacTel. While ciliary neurotrophic factor shows promise for earlier stages of MacTel, further trials are required to fully assess its long-term efficacy.